Semen Production in Sambar Stag and Response to Oestrus Synchronization in Sambar Hind - Gono Semiadi; Paul David Muir; Thomas Neville Barry; Geoff Asher (Media Veteriner, 1998)
Studies on the production of spermatozoa and oestrus synchronization in sambar deer (Cervus unicolor) were conducted using nine stags and 12 hinds. Prior to the semen collection via electroejaculator stimulation, stags were sedated using a combination of fentanyl citrate, azaperone and xylazine hydrochloride (Fentazin®, Parnell Lab. NZ). Collected semen were evaluated for its volume, motility and concentration. Collected semen were evaluated for its volume, motility and concentration, placed into straw and then kept in frozen, chilled and fresh container. In hinds, the synchronization was conducted using intravaginal Controlled Internal Drug Release type G (CIDR-G®, 9 % w/w, 300 mg progesterone; Agricultural Division, CHH Products Group Ltd, Hamilton, NZ), followed by i.m injection of 250 IU PMSG. The results showed that stags and hind did not responp very well to all treatments. Mean of ejaculated semen volume was low (0.91 ml) and some ejaculated semen had 80 % motility. Any semen collection should be conducted based on the individual performance, with the age time in hard antler condition as the main factors. Half of the hinds responded to the synchronization 59.5 hrs after the injection of PMSG.